Badges and similar student populations in different careers aspects: First sociodemographic and psychosocial references - Gómez, Sandra María (2015)
The investigated problem relates to the need to know the characteristics of the young people attending the first course of university life. It seeks to explain some sociodemographic reference to them in order to identify experiences and changes that occur during the first two years studied. These references enable to show how they build their own university life provisions, new context will demand changes in the way to perceive, see, think and act different from their own secondary level. The research methodology is qualitative and quantitative, selecting as instruments of data collection survey, individual interviews and group interviews. We worked with populations sophomores of different careers belonging to a University of Cordoba.